The Impact of Mind Mapping Technique on EFL Learners’ to Teach Vocabulary - Indani, Nirfa; Sakkir, Geminastiti; G, Hasriani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research investigates the impact of the mind mapping technique on enhancing students’ vocabulary achievement. Employing a pre-experimental research design, data were gathered through the administration of pre-tests and post-tests. The study population consisted of eleventh-grade students from SMPN 1 Tellu Limpoe, with a sample of 30 students selected through cluster random sampling. The findings reveal a statistically significant improvement in vocabulary achievement following the implementation of the mind mapping technique. The results of the T-test analysis show a T-value of 0.001, which is considerably lower than the predetermined significance level of 0.05, indicating a meaningful effect. Furthermore, the N-Gain score analysis categorizes the level of improvement as a medium category. These outcomes suggest that the mind mapping technique contributes significantly to enhancing students’ vocabulary achievement.